Effect of microstructure on machinability of extruded and conventional H13 tool steel - Kolomý, Štěpán; Malý, Martin; Doubrava, Marek; Sedlák, Josef; Zouhar, Jan; Čupera, Jan (ELSEVIER SCI LTD, 2025)
H13 tool steel samples were fabricated using material extrusion to explore their machinability, offering a promising alternative to laser powder bed fusion for producing complex parts like moulds and cores. Three material states were studied: as-built (AB), heat-treated additively manufactured (HTAM), and heat-treated wrought (HTW). Machining tests focused on cutting speed, feed per tooth, and cooling conditions (dry/flood), while tracking their effect on cutting forces, surface roughness, hardness, microstructure, and residual stresses. Heat treatment significantly reduced porosity (similar to 45 % decrease between AB and HTAM) and transformed the microstructure to full martensite, increasing hardness and cutting forces. Interestingly, the HTAM sample showed lower cutting forces than HTW-by 23.7 % in dry and 24.5 % under flood cooling. HTW generally produced smoother surfaces at lower cutting parameters, but its roughness increased at higher conditions compared to HTAM. The softest AB sample experienced the highest surface hardening (similar to 12 %) when machined at low cutting speeds, while the HTW sample showed most uniform plastic deformation, extending up to similar to 50 mu m below the surface. Dominantly tensile residual stresses were measured in HTW, while AB and HTAM showed mainly compressive residual stresses under dry conditions. This study highlights viability of extruded H13 for industrial use, particularly in mould applications.

H13 tool steel samples were fabricated using material extrusion to explore their machinability, offering a promising alternative to laser powder bed fusion for producing complex parts like moulds and cores. Three material states were studied: as-built (AB), heat-treated additively manufactured (HTAM), and heat-treated wrought (HTW). Machining tests focused on cutting speed, feed per tooth, and cooling conditions (dry/flood), while tracking their effect on cutting forces, surface roughness, hardness, microstructure, and residual stresses. Heat treatment significantly reduced porosity (similar to 45 % decrease between AB and HTAM) and transformed the microstructure to full martensite, increasing hardness and cutting forces. Interestingly, the HTAM sample showed lower cutting forces than HTW-by 23.7 % in dry and 24.5 % under flood cooling. HTW generally produced smoother surfaces at lower cutting parameters, but its roughness increased at higher conditions compared to HTAM. The softest AB sample experienced the highest surface hardening (similar to 12 %) when machined at low cutting speeds, while the HTW sample showed most uniform plastic deformation, extending up to similar to 50 mu m below the surface. Dominantly tensile residual stresses were measured in HTW, while AB and HTAM showed mainly compressive residual stresses under dry conditions. This study highlights viability of extruded H13 for industrial use, particularly in mould applications.
Effect of microstructure on machinability of extruded and conventional H13 tool steel
Keywords: H13 tool steel; Material extrusion; Heat treatment; Machinability; Microstructure; Residual stresses; H13 tool steel; Material extrusion; Heat treatment; Machinability; Microstructure; Residual stresses